Randomized controlled trial comparing outcome of intramedullary nailing versus percutaneous locked plating of extra-articular proximal tibial fractures - Chaudhary, Pashupati; Shrestha, B P; Khanal, G K; Rijal, R; Maharjan, R (Health Renaissance, 2017)
Background: Extra-articular fracture of proximal tibia is one of common injury.The study is randomized controlled trial in which individuals sustaining a fracture of the proximal metaphysis of the tibia will be operatively managed by one of two strategies. The first strategy involves fixation of the fracture with a reamed, interlocking intramedullary nail (Nail Group). The second treatment strategy involves percutaneous fixation of the fracture with a locking plate (Plate Group). Objective: To compare the functional outcome of intramedullary nailing versus percutaneous locked plating of extra-articular proximal tibial fractures in adults in terms of procedure time, time to achieve union, functional outcome, blood loss, cost of treatment, complication if any. Methods: It is randomised controlled trial study. The patients were randomized into two groups, each of size 60: Group A (IMIL group) Group B (Locking Plate group). During procedure patients were evaluated for blood loss, procedure time or any complications. Immediate post operative complications were taken into account and post operative radiological parameters measured. Results: A total of 120 patients (75 male and 45 female) were included in the study. Fifty five patients were less than 25 years age group followed by 30 patients between 25-40 yrs, 25 patients less than 25 age group and 10 patients more than 55 years. The average blood loss is 95 ml in IMIL group and 105 ml in locked plate group. Conclusion: IMIL is more expensive than percutaneous locked plates IMIL came out as a shorter surgery with little blood loss however at the same time much costlier to locked plating. Health Renaissance 2015;13 (3):